440 Desmoid tumor of the breast after mastectomy for breast cancer, a case report. (13th November 2020) - Gomez, M; Mehta, R
Abstract : Introduction: Desmoid type fibromatosis from the breast is an extremely rare benign tumor (representing <1% of all breast tumors). It arises in the deep soft tissues and originates from fibroblasts and myofibroblast. This type of tumor has no metastatic potential, but it is known to be locally aggressive with high recurrence potential. It presents a diagnostic challenge as it cannot be accurately differentiated from carcinoma based on imaging alone; therefore, histological evaluation is imperative for its diagnosis and further treatment. Case: We present a case of a 52-year-old female with a history of invasive ductal carcinoma treated with bilateral mastectomy, who underwent an MRI for surveillance showing a 4 cm mass on her right chest wall highly suspicious for recurrent breast carcinoma. Subsequent excision was performed showing a desmoid-type fibromatosis with negative margins. Conclusion: While this type of tumor is benign, given its infiltrative characteristics and limitation on radiographic diagnosis, surgical excision with clear margins is essential to reduce the risk of local recurrence and to rule out a malignant entity.